2016
DOI: 10.1167/iovs.16-20560
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo 3-Dimensional Strain Mapping Confirms Large Optic Nerve Head Deformations Following Horizontal Eye Movements

Abstract: Our results confirm that horizontal eye movements generate significant ONH strains, which is consistent with our previous estimations using finite element analysis. Further studies are needed to explore a possible link between ONH strains induced by eye movements and axonal loss in optic neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
123
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 30 publications
(46 reference statements)
10
123
1
3
Order By: Relevance
“…However, the difference in ppS stresses was relatively large (ppS stress in adduction was 16% higher than in abduction). This trend was similar to our previous studies, 14,16 in which LC strains in adduction were higher than those in abduction. Other independent studies also concluded that ONH deformation was more affected by adduction.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, the difference in ppS stresses was relatively large (ppS stress in adduction was 16% higher than in abduction). This trend was similar to our previous studies, 14,16 in which LC strains in adduction were higher than those in abduction. Other independent studies also concluded that ONH deformation was more affected by adduction.…”
Section: Discussionsupporting
confidence: 92%
“…41 The shearing deformation observed in this study (Fig. 2) and other OCT observations [13][14][15] might be able to explain the optic disc rotation about the vertical axis (axis along the superior-inferior direction) observed in myopic eyes. 42 It is plausible that continuous stretching of peripapillary tissues following repeated eye movements might contribute to the development of rotated optic discs and peripapillary zones simultaneously through a tissue remodeling process.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations